2005
DOI: 10.1093/humrep/dei288
|View full text |Cite
|
Sign up to set email alerts
|

Repeated testing of basal FSH levels has no predictive value for IVF outcome in women with elevated basal FSH

Abstract: BACKGROUND: It is a common practice to repeatedly test the level of basal FSH early in the cycle and to start IVF treatment only when the FSH level is below a certain threshold value. This is based on the idea that these women will respond better to ovarian stimulation when the basal FSH level is lower at the start of the cycle. The aim of this study is to assess the value of this practice. The results of this study reveal that women who are poor responders or with reduced ovarian reserve have a poor outcome a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 17 publications
1
15
1
Order By: Relevance
“…For women experiencing infertility, various indicators of ovarian age are commonly used to guide IVF=ICSI treatment. These include antral follicle count (AFC), 31-33 FSH, 22,35 LH, 32,36 inhibin B, 34 E 2 , 32,33,37 and progesterone 33 levels. Other factors that may influence the success of IVF=ICSI treatment include sperm quality indices, duration of infertility, and uterine health.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For women experiencing infertility, various indicators of ovarian age are commonly used to guide IVF=ICSI treatment. These include antral follicle count (AFC), 31-33 FSH, 22,35 LH, 32,36 inhibin B, 34 E 2 , 32,33,37 and progesterone 33 levels. Other factors that may influence the success of IVF=ICSI treatment include sperm quality indices, duration of infertility, and uterine health.…”
Section: Discussionmentioning
confidence: 99%
“…21 Therefore, indicators of IVF=ICSI treatment success include both process measures (e.g., oocytes retrieved, oocytes fertilized) and outcome measures (e.g., embryo quality, pregnancy, miscarriage, live birth). 22 In the present study, a retrospective cohort analysis was conducted to examine the effect of PCOS on process and outcome measures of IVF=ICSI treatment success. Patient data were obtained from existing records at a major fertility treatment center.…”
mentioning
confidence: 99%
“…However, it has been suggested that some clinics use basal FSH as a screening tool and refuse to treat patients with elevated basal FSH, to maintain the clinic's overall success rate or to improve their position on the league tables (23). We reported elsewhere that women with elevated basal FSH, especially younger women, still can achieve a lower, but respectable, live birth rate with IVF treatment (7) and that repeatedly testing their basal FSH levels is of no clinical value (24).…”
Section: Discussionmentioning
confidence: 99%
“…These include ovarian stimuation, oocyte retrieval, fertilization in a liquid medium, embryo selection and embryo transfer into a uterine environment (Knochenhauer et al 1998). Therefore, indicators of IVF/ICSI treatment success include process (number and quality of oocytes retrieved, inseminated and fertilized) as well as outcome (pregnancy, miscarriage and live birth rates) measures (Abdalla and Thum 2006). …”
Section: Introductionmentioning
confidence: 99%